The Functionality of Facial Appearance and Its Importance to a Korean Population - Kim, Young Jun (The Korean Society of Plastic and Reconstructive Surgeons, 2013)
BACKGROUND: Many people have an interest in the correction of facial scars or deformities caused by trauma. The increasing ability to correct such flaws has been one of the reasons for the increase in the popularity of facial plastic surgery. In addition to its roles in communication, breathing, eating, olfaction and vision, the appearance of the face also plays an important role in human interactions, including during social activities. However, studies on the importance of the functional role of facial appearance. As a function of the face are scare. Therefore, in the present study, we evaluated the importance of the functions of the face in Korea. METHODS: We conducted an online panel survey of 300 participants (age range, 20-70 years). Each respondent was administered the demographic data form, Facial Function Assessment Scale, Rosenberg Self-Esteem Scale, and standard gamble questionnaires. RESULTS: In the evaluation on the importance of facial functions, a normal appearance was considered as important as communication, breathing, speech, and vision. Of the 300 participants, 85% stated that a normal appearance is important in social activities. CONCLUSIONS: The results of this survey involving a cross-section of the Korean population indicated that a normal appearance was considered one of the principal facial functions. A normal appearance was considered more important than the functions of olfaction and expression. Moreover, a normal appearance was determined to be an important facial function for leading a normal life in Korea.